Return migration and its consequences in Southeast Europe - Jusufi, Lumnije 1977-; Dimova, Rozita; Čapo, Jasna 1961- (Peter Lang, 2024)
This volume is a collection of papers presented at the 60th International Academic Week organized by the Southeast Europe Association in October 2022. The event brought together scholars to discuss the various facets of international return migration from diverse destination countries back to Southeast Europe. Within this volume, the concept of return takes on a dynamic and multifaceted character. It is seen not as a one-way journey but as an ongoing, non-linear, and reversible process consisting of multiple stages. This approach recognizes that migration is a journey with many dimensions, involving mobility in various directions. The volume sheds light on a variety of migration practices to and from Southeast Europe, revealing a complex interplay of movements over time.